Cryopreservation and xenografting of human ovarian fragments: medulla decreases the phosphatidylserine translocation rate. Issue 1 (December 2016) - Isachenko, Vladimir; Todorov, Plamen; Isachenko, Evgenia; Rahimi, Gohar; Hanstein, Bettina; Salama, Mahmoud; Mallmann, Peter; Tchorbanov, Andrey; Hardiman, Paul; Getreu, Natalie; Merzenich, Markus
Abstract Background Phosphatidylserine is the phospholipid component which plays a key role in cell cycle signaling, specifically in regards to necrosis and apoptosis. When a cell affected by some negative factors, phosphatidylserine is no longer restricted to the intracellular side of membrane and can be translocated to the extracellular surface of the cell. Cryopreservation can induce translocation of phosphatidylserine in response to hypoxia, increasing intracellular Ca2+, osmotic disruption of cellular membranes, generation of reactive oxygen species and lipid peroxidation. As such the aim of this study was to test the level of phosphatidylserine translocation in frozen human medulla-contained and medulla-free ovarian tissue fragments. Methods Ovarian fragments from twelve patients were divided into small pieces of two types, medulla-free cortex (Group 1, n = 42, 1.5–3.0 × 1.5–3.0 × 0.5–0.8 mm) and cortex with medulla (Group 2, n = 42, 1.5–3.0 × 1.5–3.0 × 1.5–2.0 mm), pre-cooled after operative removal to 5 °C for 24 h and then conventionally frozen with 6 % dimethyl sulfoxide, 6 % ethylene glycol and 0.15 M sucrose in standard 5-ml cryo-vials. After thawing at +100 °C and step-wise removal of cryoprotectants in 0.5 M sucrose, ovarian pieces were xenografted to SCID mice for 45 days. The efficacy of tissues cryopreservation, taking into account the presence or absence of medulla, was evaluated by the development of follicles (histology with hematoxylin-eosin) and through the intensity of translocation of phosphatidylserine (FACS with FITC-Annexin V and Propidium Iodide). Results For Groups 1 and 2, the mean densities of follicles per 1 mm3 were 9.8, and 9.0, respectively. In these groups, 90 and 90 % preantral follicles appeared morphologically normal. However, FACS analysis showed a significantly decreased intensity of translocation of phosphatidylserine (FITC-Annexin V positive) after cryopreservation of tissue with medulla (Group 2, 59.6 %), in contrast with tissue frozen without medulla (Group 1, 78.0 %, P < 0.05). In Groups 1 and 2 it was detected that 21.6 and 40.0 % cells were viable (FITC-Annexin V negative, Propidium Iodide negative). Conclusion The presence of medulla in ovarian pieces is beneficial for post-thaw development of cryopreserved human ovarian tissue.